Dopamine Agonists for Pituitary Adenomas - Cooper, Odelia; Greenman, Yona (Frontiers in Endocrinology, 2018)
Dopamine agonists (DA) are well established as first-line therapy for prolactinomas. These tumors express high levels of dopamine 2 receptors (D2R), leading to the strong efficacy of DA in reducing tumor size and hormonal secretion. Other pituitary tumor subtypes express D2R to varying degrees, leading to an extensive body of research into potential off-label use of DA in non-prolactinoma pituitary tumors. Preclinical models of Cushing’s disease, acromegaly, and nonfunctioning pituitary tumors (NFPT) demonstrate D2R expression in cell lines and cultured tumors as well as effectiveness of DA in reducing hormonal secretion in functioning tumors and arresting tumor proliferation. Clinical studies have shown some efficacy of DA in treatment of these tumors. In Cushing’s disease, DA therapy results in normalization of urinary cortisol levels in approximately 25% of patients, and may result in decreased tumor size; in acromegaly, DA therapy leads to normalization of insulin-like growth factor I and tumor shrinkage in approximately one-third of patients, and improved responses when used in combination with somatostatin receptor ligands. Among patients with NFPT, pooled results show 30% experience reduction of tumor size and 58% show stabilization of disease. Targeting D2R in pituitary tumors appears to have some clinical benefit in patients and presents an option for a well-tolerated medical therapy.